Procesy eneolityzacji Europy – wybrane zagadnienia - Kadrow, Sławomir (Acta Universitatis Lodziensis. Folia Archaeologica, 2011)
E. Neustupný suggested using a term “Eneolithic” instead of the copper age and replacing its distinctive raw material criterion (copper) by a complex of cultural, social and economic elements. Importantly he recognized the emergence of the plough in agronomy instead of burning techniques, the replacement of large settlements by smaller ones, burying the dead in cemeteries on land outside the inhabited areas and the strengthening role of the male (“patriarchy”) in societies of that time. A sequence of the Hamangia-Varna cultures, beginning from the 3rd development phase of the former, is thought to be the oldest and most representative cultures of the copper age/eneolithic. They are dated from 4900 to 4400 BC. The wealthiest in metal product sites is an eponymic cemetery at Varna. All metal artifacts from the graves of the Hamangia and Varna cultures maybe qualied to a group of symbolic finds, which had little in common with the notion of utilitarism. Similar functions were performed by other artifacts made of different raw materials. Among others, long int blades or ornaments made of Spondylus shells and many others may be mentioned. It is thought that in the cemeteries of the Hamangia-Varna cultures circle, with particular consideration of the cemetery at Varna, there were traces of serious inner differentiation of societies that were using it. In the middle of the 5th millennium BC on the Atlantic coast of the south-western Brittany in the Gulf of Morbihan, grave complexes and deposits with numerous artifacts were found, which represented the above mentioned category of symbolic finds. Jadeite axes are very numerous among the artifacts. In one grave alone, over 100 specimens of these axes were discovered. The graves also contained variscite beads. Jadeite was imported from the Italian Alps and from Liguria, and variscite from north-west Spain. What is interesting is that the graves did not contain any metal artifacts (copper or gold). Huge graves with richly furnished male burials and vast megalithic structures lead us to believe that within the Castellic culture advanced forms of political organization existed. The oldest eneolithic centres (fig. 1) formed on economically wealthy, populous Mesolithic settlement agglomerations (Dobruja, Brittany) with the participation of inuences of contemporaneous early Neolithic cultures. There is material evidence of contacts among these centres. There are literary statements alluding to the steepe occurrence of the oldest eneolithic centre in Dobruja, of which there is no grounded evidence, and they do not have theoretical support either. Instead, they are based on a highly popular myth of the so-called indoeuropeization of the “old Europe”. A creative synthesis of experiences of local Mesolithic and Neolithic populations caused the occurrence of differentiation in respect of gender burial ritual on the west coast of the Black Sea, and then a rapid demand for objects of prestige (made of gold, copper, stone, shell, etc.), owing to which males legitimized their privileged social status. These changes were probably justied in respect of religion and world-view on the one hand by the oldest manifestations of emerging inadvertently individualistic chivalric code, and, on the other hand, by the development of the megalithic idea, manifesting group (ancestral) ties focused around the cult of ancestors in the Gulf of Morbihan in Brittany on the Atlantic coast. In the latter case, the males legitimized their status using, most of all, jadeite axes in rituals. Similar mechanisms caused the emergence of the oldest phases of the Funnel Beaker Culture in the south-west-Baltic area about 500 years later. The local south Scandinavian population was inspired mainly by the Atlantic experiences. This is testied by numerous jadeite axes, which performed mostly symbolic (prestigious) functions and by the adaptation of the megalithic idea. The Eneolithization of the fully developed Neolithic societies in the Balkans, the Carpathian Valley, the right-bank Ukraine and in Moldavia, central and western Europe, which took place as early as the 2nd half of the 5th millennium BC took a different course and had a different character. It consisted in more or less a superficial adaptation of one of “patriarchal” ethos radiating from two centres of the oldest eneolithic in Dobruja and Brittany. What concerns the material culture is it manifested itself in, is the adaptation of copper or jadeite axes and hatchets. As far as the rituals are concerned it showed itself in the spread of individual, differentiated in respect of gender, burials from the west–Black Sea centre or collective megalithic burials from the West. The Late Neolithic societies from the Great Hungarian Plain played an important role in the propagation of eneolithization in central-eastern Europe. Concentrating on multidirectional cultural inuences, they inuenced the neighbouring areas. On the one hand this facilitated the original adaptation of the early Neolithic inuences from the west coast of the Black Sea, and on the other – contributed to popularization of this version of Neolithization in other areas (e. g. to the north of the Carpathians in Volhynia and in Little Poland and in some sense also in Kuyavia).